Transarterial Embolisation for Intractable Haematuria: A Case Report and Review of Management Strategies - Aisyah Amalia; Achmad Bayhaqi Nasir Aslam; Farah Nurdiana; Siswidiyati (Asian Journal of Health Research, 2025)
Introduction: Refractory gross haematuria is a significant urological emergency, characterised by prolonged and life-threatening bleeding that does not respond to standard treatment. The main recognised aetiologies encompass malignant neoplasms of the bladder and haemorrhagic cystitis. When conservative treatments and intravesical medications fail, transarterial embolisation (TAE) is a dependable and effective technique for achieving haemostasis. This study aims to report cases of haematuria resulting from bladder pathology, the role of interventional radiology in embolisation, and technical considerations. Case Presentation: We present two cases of refractory gross haematuria from the bladder managed with TAE. Case 1 involved a 65-year-old male with locally advanced, hypervascularised bladder squamous cell carcinoma (cT4aN3M1b). Case 2 involved a 69-year-old woman with haemorrhagic cystitis secondary to pelvic radiotherapy for stage IVb cervical carcinoma. Pre-embolisation angiography showed prominent blushing of feeder arteries arising from the superior vesical artery (SVA) bilaterally. Embolisation used gelfoam and PVA particles. The procedure reduces tumour blushing (Case 1) and hypervascularisation (Case 2), controlling haematuria. Conclusion: TAE is a safe and effective treatment modality for managing persistent gross haematuria due to diverse bladder pathologies, including bladder malignancy and radiation cystitis. Bilateral vesical artery embolisation was performed in both cases to ensure a more sustained response and reduce the likelihood of recurrence.